Step down to 6 months of prophylactic‐dose low molecular weight heparin after initial full‐dose anticoagulation for the treatment of cancer‐associated thrombosis (STEP‐CAT): A pilot study. (9th June 2022) - Popov, Jesse; Coelho, Suellen; Carrier, Marc; Sperlich, Catherine; Solymoss, Susan; Routhier, Nathalie; Shivakumar, Sudeep; Aibibula, Wusiman; Kahn, Susan R.; Tagalakis, Vicky
Abstract: Background: Patients with cancer‐associated thrombosis (CAT) are treated with full‐dose anticoagulation for at least 3 months, but optimal dosing thereafter is unknown. Aim: We explored the feasibility of extended prophylactic‐dose low molecular weight heparin (LMWH) treatment following a minimum of 3 months of full‐dose LMWH. Methods: We conducted a multicenter prospective pilot study of patients with CAT who completed at least 3 months of therapeutic‐dose LMWH. Patients received 6 months of prophylactic‐dose subcutaneous enoxaparin (40 mg once daily). The primary outcome was recurrence of deep vein thrombosis (DVT) or pulmonary embolism (PE), and secondary outcomes included major, clinically relevant non‐major (CRNM), and minor bleeding. Results: From August 2016 to May 2019, 52 patients with a mean age of 64.1 years were included. The study was stopped early because of poor recruitment. Breast (23.1%) and colorectal (19.2%) were the most common cancers, and 61.0% had stage IV malignancy. Index CAT consisted of DVT alone in 57.7% of patients and pulmonary embolism (PE) with or without DVT in 42.3%. Patients received a mean of 7.6 months of weight‐adjusted LMWH before enrollment. During a mean follow‐up of 5.6 months, one patient was diagnosed with recurrent incidental PE (0.0035 events/subject‐month). There were no major bleeding events, one CRNM, and one minor bleeding event. Eight (15.4%) patients died; six from cancer and two from respiratory disease unrelated to PE. Conclusions: These results, in part, provide support for trials of extended reduced‐dose anticoagulation for the secondary prevention of CAT. (ClinicalTrials.gov : NCT02752607)